Can a Minimum Wage Increase Have an Adverse Impact on Inequality? Evidence from Two Latin American Economies - Angel-Urdinola, Diego F. (2012)
This paper uses a semiparametric model to analyze the impact of an increase in the real minimum wage on inequality in Colombia between 1995 and 1999 and in Paraguay between 1993 and 2000-2001. Simulations suggest that if the employment effects of the minimum wage increase are ignored, the underlying policies would contribute to reduce earnings inequality in Colombia and would be inequality neutral in Paraguay. By considering the drop in wages of those who lost their jobs, simulations suggest that in both countries the policy in question would increase earnings inequality under some assumptions about the employment elasticity of the minimum wage and the new level of earnings unemployed workers rely upon. While these findings do not mean that minimum wage increases in LDCs (Less Developed Countries) necessarily have adverse distributional affects, they suggest that minimum wage policy should be implemented with care depending on how sensitive employment is to wage increases.